Hubungan Acute Coronary Syndrome dengan nilai Low Density Lipoprotein Cholesterol dan Monosit Darah Tepi - Shifa Khairunnisa Azzahra (Jurnal Riset Kedokteran, 2024)
Abstract. Heart function decreased on contraction initiate complication evenmore chronic disease that causing sudden death. This study aims to analyze the correlation of Acute Coronary Syndrome (ACS) with the value of Low Denstity Lipoprotein Cholesterol (LDL Cholesterol) and Peripheral Blood Monocytes. Medical record data was obtained based on patient characteristics throught out diganosis criteria and result of complete blood count (CBC) specific in leukocyte differential count qualify hematology test in laboratory examination total of 60 patients as subjects by devide into groups 30 patients of ACS and 30 patients of Non-ACS. Nominal ACS was calculated by comparing ratio of LDL Cholesterol and Peripheral Blood Monocytes in the incidence of Acute Coronary Syndrome (ACS). The dependent variable lead to both of those two independent variable analyzed by statistical independent t-test with confidence interval in 95%. Output of this reasearch guide to characterics of ACS, those represent men in majority with the most common by patients in elderly age >60 years based on subject diagnosed with ACS and Non-ACS. Independent t-test point there is significant (Pvalue = 0.00) correlation between the value of Low Density Lipoprotein Cholesterol (LDL Cholesterol) and Peripheral Blood Monocytes with the prevalence Acute Coronary Syndrome (ACS) in the ICCU of RSUD R. Syamsudin SH Sukabumi. Abstrak. ACS terbagi menjadi Non-ST Elevation Myocardial Infarction (NSTEMI), dan Unstable Angina Pectoris (UAP). Penelitian ini bertujuan untuk menganalisis hubungan Acute Coronary Syndrome (ACS) dengan nilai Low Density Lipoprotein Cholesterol (LDL Cholesterol) dan Monosit Darah Tepi. Data rekam medis yang diperoleh berdasarkan karakteristik pasien melalui kriteria diagnosis dan hasil pemeriksaan hematologi rutin dari laboratorium dengan jumlah subjek sebanyak 60 pasien 30 pasien ACS dan 30 pasien Non-ACS. Prevalensi ACS dihitung dengan membandingkan antara rasio LDL Cholesterol dan rasio Monosit. Hubungan nilai LDL Cholesterol dan Monosit Darah Tepi dengan kejadian ACS dianalisis dengan menggunakan uji statistik independent t-test pada tingkat kepercayaan 95%. Hasil penelitian didapatkan pasien ACS lebih banyak pada laki- laki dengan usia pasien >60 tahun pada subjek didagnosis ACS dan Non-ACS. Independent t-test menunjukkan terdapat hubungan nilai LDL Cholesterol dan Monosit Darah Tepi dengan kejadian ACS (Pvalue = 0.000).